Persuasão e dinamismo psíquico: investigações na história da cultura ocidental - Marina Massimi (Arquivos Brasileiros de Psicologia, 2008)
The purpose is to prove, from a multidisciplinary and historical perspective, the process that transformed the persuasion addressee - from an active and critical subject into a passive product consumer. In Western culture history, two different concepts regarding the persuasion process are opposed: on one side, it is understood that persuasion should provide the subject with an experience, and that subject is acknowledged as an active and intentional receiver of the stimuli from the external world, a live and spiritual body (with abilities of judgment and making decisions); on the other side, persuasion is seen as the induction of an experience on a subject considered a mere passive receptor of external stimuli, a body determined by the mechanism of reactions.